2010
DOI: 10.1007/s00423-009-0576-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancellations of (helicopter-transported) mobile medical team dispatches in the Netherlands

Abstract: BackgroundThe trauma centre of the Trauma Center Region North-West Netherlands (TRNWN) has consensus criteria for Mobile Medical Team (MMT) scene dispatch. The MMT can be dispatched by the EMS-dispatch centre or by the on-scene ambulance crew and is transported by helicopter or ground transport. Although much attention has been paid to improve the dispatch criteria, the MMT is often cancelled after being dispatched. The aim of this study was to assess the cancellation rate and the noncompliant dispatches of ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 30 publications
2
28
1
2
Order By: Relevance
“…Our proportion of cancelations compares well with similar services 10, 11. Among several reasons for cancelations, the most common was “no indication,” especially at night.…”
Section: Discussionsupporting
confidence: 74%
“…Our proportion of cancelations compares well with similar services 10, 11. Among several reasons for cancelations, the most common was “no indication,” especially at night.…”
Section: Discussionsupporting
confidence: 74%
“…Although it is recognized that this triage method will result in over-triage and over-cancellation of HEMS, a certain amount of over-triage is deemed necessary. Giannakopoulos and colleagues 16 have reported that a low HEMS activation threshold prior to evaluating patients at the scene (Primary Launch Criteria) resulted in a 43.5% flight cancellation rate and 4.0% under-triage. They concluded that this combination of over-triage (cancellation) and under-triage were acceptable and that the additional costs of cancelled missions were within an acceptable range.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Dutch HEMS are associated with high levels of primary overtriage, resulting in cancellation of the missions by the already on-scene ground ambulance, before HEMS even arrives on the scene of the accident 9. In our trauma system there is no consensus about standardised criteria for cancelling deployed HEMS.…”
mentioning
confidence: 94%